Quarry - Franco, Tanis (Brave & brilliant series., 2018)
Spaces are not exterior to bodies. They influence and affect the way bodies exist in the world. A quarry is an unnatural place within a natural territory. At any moment, it can be abandoned. A body is not separate from the spaces it inhabits. They exist together, in a mutual state of interrelation and instability. Quarry relays a year in the life of a body in transition as it changes with other bodies; human, animal, and mineral. It examines queer social spaces and contested natural spaces, asking how they affect each other. Using evocative metaphor and refreshing language, these poems make bodily experience new. Tanis Franco eschews traditional narratives of the queer and transgender body, bringing nuanced ideas to an ongoing literary and philosophical conversation. Their strong sense of location and landscape is interwoven with sensual language and impeccable craft, creating a unique and distinctive voice.